CARACTERIZAÇÃO FÍSICO-QUÍMICA DO SOLO NA CULTURA DE TIFTON 85 NO PRIMEIRO ANO DE ESTABELECIMENTO - Porazzi, Cláudio C.; Fernandes, Sandra B. V.; Bergoli, Luís M. G.; Uhde, Leonir T.; Garcia, Dagmar C.; Londero, Ana L. (Salão do Conhecimento, 2013)
Resumo